Effects of de-industrialization on unemployment, re-employment, and work conditions in a manufacturing workforce - Teschke Kay; Demers Paul; Kelly Shona; Hershler Ruth; Ostry Aleck S; Hertzman Clyde (BMC, 2001)
Abstract Background The purpose of this study was to investigate the impact of a 20-year process of de-industrialization in the British Columbia (BC) sawmill industry on labour force trajectories, unemployment history, and physical and psychosocial work conditions as these are important determinants of health in workforces. Methods The study is based on a sample of 1,885 respondents all of whom were sawmill workers in 1979, a year prior to commencement of de-industrialization and who were followed up and interviewed approximately 20 years later. Results Forty percent of workers, 64 years and under, were employed outside the sawmill sector at time of interview. Approximately one third of workers, aged 64 and under, experienced 25 months of more of unemployment during the study period. Only, 1.5% of workers were identified as a "hard core" group of long-term unemployed. Workers re-employed outside the sawmill sector experienced improved physical and psychosocial work conditions relative to those employed in sawmills during the study period. This benefit was greatest for workers originally in unskilled and semi-skilled jobs in sawmills. Conclusions This study shows that future health studies should pay particular attention to long-term employees in manufacturing who may have gone through de-industrialization resulting in exposures to a combination of sustained job insecurity, cyclical unemployment, and adverse physical and psychosocial work conditions.